Information Processing And Technology Transfer In A Developing Country - Harry A. Carey (Journal of Applied Communications, 1988)
The Pennsylvania State University, along with Tennessee State University, is contractor on the USAID-funded Swaziland Cropping Systems Research and Extension Training Project. In addition to research and Extension objectives, Penn State University staff designed and implemented an information component for the Swaziland Ministry of Agriculture and Cooperatives. The evolving information system is interactive, involving many people from the researcher to the Swazi farmer. This helps insure the usefulness of educational programs and materials. A cooperative training effort helps Extension field staff understand technical recommendations, use educational materials generated by the Information Section, and improve delivery of educational programs. This information/extension system is becoming increasingly effective in delivering practical recommendations that are useful for increasing farm productivity.